Sildenafil for pulmonary hypertension complicating bronchopulmonary dysplasia. Issue 4 (July 2014) - Bhatt-Mehta, Varsha; Donn, Steven M
<x xml:space="preserve">Abstract</x> Sildenafil, a phospohodiesterase-5 inhibitor, is widely used to treat pulmonary hypertension in infants with bronchopulmonary dysplasia despite a lack of evidence to support either safety or efficacy and US FDA advice against its use.